Lead and Cadmium Levels in Urine of Sanitation Workers: Kadar Timbal dan Kadmium pada Urine Petugas Kebersihan - Mochamad Hidayah; Galuh Ratmana Hanum (Academia Open, 2023)
General Background the exposure of waste management workers to heavy metals, particularly lead (Pb) and cadmium (Cd), poses significant health risks, especially among active and passive smokers. Specific Background this study aims to assess the levels of Pb and Cd in the urine of cleaning personnel working in waste disposal areas, distinguishing between active and passive smokers. Knowledge Gap limited research exists on the impact of smoking status on heavy metal accumulation in waste management workers. Aims the research focuses on determining the concentration of Pb and Cd in urine samples and understanding the potential health implications. Results findings indicate that the highest Pb level was 0.113 mg/L in passive smokers, while the lowest was 0.031 mg/L in active smokers. Novelty the study highlights the lack of correlation between Pb and Cd levels among active and passive smokers in this population. Implications these results underscore the need for regular monitoring of heavy metal exposure among waste management workers to mitigate health risks associated with environmental contaminants. Highlights: The highest lead concentration found in urine samples of passive smokers was 0.113 mg/L. All measured levels of lead and cadmium were below the established safety thresholds. No significant correlation was observed between lead and cadmium levels in active and passive smokers. Keywords: Lead, Cadmium, Waste Management, Urine Analysis, Heavy Metals